Degree of blast resistance and grain yield of improved upland rice cultivars - Prabhu, Anne Sitarama; Filippi, Marta Cristina (Pesquisa Agropecuaria Brasileira, 2001)
The aim of this work was to study the levels of leaf and panicle blast resistance and their effect on grain yield of 12 rice cultivars, in a field experiment, during consecutive three years. The degree of leaf blast and panicle blast resistance was determined by the assessment criteria of area under disease progress curve and disease severity ten days before the harvest, respectively. The cultivars Progresso, Cuiabana, Caiapó, Carajás and Araguaia were superior in descending order for leaf blast resistance. For panicle blast, Carajás and Progresso, exhibited lower disease severities than the rest of the cultivars in the first two years. The grain yields during three years ranged from 83 kg/ha for IAC 201 to 3,617 kg/ha for Rio Paraguai, and the variation was explained by blast severity, in the panicles, as the correlations were negative. The races IB-9, IB-41, IB-13 and IC-27 of Pyricularia grisea obtained from 13 cultivars showed differential interaction. These results permitted to conclude that the degree of resistance of some of the cultivars was inadequate and other measures of disease control are necessary.